A pilot study and novel angiographic classification for superior sagittal sinus stenting in patients with non-thrombotic intracranial venous occlusive disease. (12th January 2017) - Raper, Daniel M S; Buell, Thomas J; Ding, Dale; Pomeraniec, I Jonathan; Crowley, R Webster; Liu, Kenneth C
Abstract : Objective: Safety and efficacy of superior sagittal sinus (SSS) stenting for non-thrombotic intracranial venous occlusive disease (VOD) is unknown. The aim of this retrospective cohort study is to evaluate outcomes after SSS stenting. Methods: We evaluated an institutional database to identify patients who underwent SSS stenting. Radiographic and clinical outcomes were analyzed and a novel angiographic classification of the SSS was proposed. Results: We identified 19 patients; 42% developed SSS stenosis after transverse sinus stenting. Pre-stent maximum mean venous pressure (MVP) in the SSS of 16.2 mm Hg decreased to 13.1 mm Hg after stenting (p=0.037). Preoperative trans-stenosis pressure gradient of 4.2 mm Hg decreased to 1.5 mm Hg after stenting (p<0.001). No intraprocedural complication or junctional SSS stenosis distal to the stent construct was noted. Improvement in headache, tinnitus, and visual obscurations was reported by 66.7%, 63.6%, and 50% of affected patients, respectively, at mean follow-up of 5.2 months. We divided the SSS into four anatomically equal segments, numbered S1–S4, from the torcula to frontal pole. SSS stenosis typically occurs in the S1 segment, and the anterior extent of SSS stents was deployed at the S1–S2 junction in all but one case. Conclusions: SSS stenting is reasonably safe, may improve clinical symptoms, and significantly reduces maximum MVP and trans-stenosis pressure gradients in patients with VOD with SSS stenosis. The S1 segment is most commonly stenotic, and minimum pressure gradients for symptomatic SSS stenosis may be lower than for transverse or sigmoid stenosis. Additional studies and follow-up are necessary to better elucidate appropriate clinical indications and long-term efficacy of SSS stenting.